2001
DOI: 10.1523/jneurosci.21-03-01067.2001
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Basic Membrane Properties of Postnatal Gonadotropin-Releasing Hormone Neurons in the Mouse

Abstract: The electrophysiological characteristics of unmodified, postnatal gonadotropin-releasing hormone (GnRH) neurons in the female mouse were studied using whole-cell recordings and single-cell RT-PCR methodology. The GnRH neurons of adult animals fired action potentials and exhibited distinguishable voltage-current relationships in response to hyperpolarizing and depolarizing current injections. On the basis of their patterns of inward rectification, rebound depolarization, and ability to fire repetitively, GnRH n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 47 publications
6
58
0
Order By: Relevance
“…Such a scenario would be in good agreement with evidence for the expression of ER␤, but not ER␣, in GnRH neurons (Herbison and Pape, 2001). A common theme in the investigation of the GnRH neuronal phenotype is that of marked heterogeneity (Sim et al, 2001), and once again, we find here that only a subpopulation (25-40%) of all GnRH neurons, irrespective of location, respond to estrogen. Studies in mice have shown that ϳ20% of adult female GnRH neurons express ER␤ transcripts , whereas work in the rat has demonstrated 50 -80% of GnRH neurons to contain ER␤ immunoreactivity (Hrabovszky et al, 2001;Kallo et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Such a scenario would be in good agreement with evidence for the expression of ER␤, but not ER␣, in GnRH neurons (Herbison and Pape, 2001). A common theme in the investigation of the GnRH neuronal phenotype is that of marked heterogeneity (Sim et al, 2001), and once again, we find here that only a subpopulation (25-40%) of all GnRH neurons, irrespective of location, respond to estrogen. Studies in mice have shown that ϳ20% of adult female GnRH neurons express ER␤ transcripts , whereas work in the rat has demonstrated 50 -80% of GnRH neurons to contain ER␤ immunoreactivity (Hrabovszky et al, 2001;Kallo et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…These frequencies were almost similar to those for mouse GnRH neurons; in GnRH neurons derived from 11.5-day-old mouse embryos and cultured for 1-2 weeks, the frequencies of spontaneous firing rate were smaller than 4 Hz [15], and in single GnRH neurons derived from 15-20-day-old mice, the frequencies were 0.02-1.0 Hz (0.4 ± 0.1 Hz) [21,22]. Although we did not determine in the present study whether the recorded neurons were GnRH neurons or not, it is likely that each activity was recorded from 1 or at most 2 neurons.…”
Section: Discussionsupporting
confidence: 68%
“…All drugs (Tocris Biosciences) were applied to the ACSF bathing solution at the following established concentrations: apamin 300 nM (Liu and Herbison, 2008), UCL2077 10 M (Shah et al, 2006), 2-aminoethoxydiphenylborate (2-APB) 100 M (Jasoni et al, 2007), cyclopiazonic acid (CPA) 30 M (Power and Sah, 2008) and tetrodotoxin (TTX) 0.5 M (Sim et al, 2001). Apamin and TTX were dissolved in water while the others were dissolved initially in dimethylsulfoxide resulting in a final dimethylsulfoxide concentration in the perfusion solution of 0.03 to 0.1%.…”
Section: Methodsmentioning
confidence: 99%